The Cellular and Transcriptomic Early Innate Immune Response to BCG Vaccination in Mice - Liya G. Kondratyeva; Olga A. Rakitina; Victor V. Pleshkan; Alexey I. Kuzmich; Irina A. Linge; Sofia A. Kondratieva; Eugene V. Snezhkov; Irina V. Alekseenko; Eugene D. Sverdlov (Cells)
It is established that BCG vaccination results in the development of both a specific immune response to mycobacterial infections and a nonspecific (heterologous) immune response, designated as trained immunity (TRIM), to other pathogens. We hypothesized that local BCG immunization may induce an early immune response in bone marrow and spleen innate immunity cells. The early transcriptomic response of various populations of innate immune cells, including monocytes, neutrophils, and natural killer (NK) cells, to BCG vaccination was examined. To this end, C57Bl/6J mice were subcutaneously immunized with 106 CFU of BCG. Three days following BCG administration, the three cell populations were collected from the control and BCG-vaccinated groups using FACS. All cell populations obtained were utilized for the preparation and sequencing of RNA-seq libraries. The analysis of FACS data revealed an increase in the proportion of splenic NK cells and monocytes 3 days post-vaccination. Transcriptomic analysis revealed the deregulation of genes associated with the regulation of immune response (according to Gene Ontology terms) in NK cells, monocytes, and unsorted bone marrow cells. Two NK cell-specific immune ligands (Tnfsf14 and S100a8) and two bone marrow-specific immune receptors (C5ar1 and Csf2rb) were identified among differentially expressed genes. No alterations were identified in neutrophils in either their percentage or at the transcriptomic level. Thus, in this study, we demonstrated that BCG vaccination provides an early increase in the proportion of murine bone marrow and spleen immune cell populations, as well as transcriptomic alterations in monocytes, NK cells, and non-sorted bone marrow cells. This early innate immune response may be beneficial for enhancing TRIM.